2005
DOI: 10.1002/cncr.20894
|View full text |Cite
|
Sign up to set email alerts
|

Risk of childhood germ cell tumors in association with parental smoking and drinking

Abstract: BACKGROUND. The etiology of childhood germ cell tumors (GCT) is not well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
(43 reference statements)
3
18
1
Order By: Relevance
“…Paternal smoking status and postnatal environmental or chemical hazard exposure experienced, which may also be associated with some childhood tumors, also could not be measured [16,49,57,17,68]. Exposure to household pesticides and increased risk of Wilms tumor have yet to be firmly established [61,69]; however, a review of studies has described that some association exists between pesticides and childhood cancer [63].…”
Section: Discussionmentioning
confidence: 94%
“…Paternal smoking status and postnatal environmental or chemical hazard exposure experienced, which may also be associated with some childhood tumors, also could not be measured [16,49,57,17,68]. Exposure to household pesticides and increased risk of Wilms tumor have yet to be firmly established [61,69]; however, a review of studies has described that some association exists between pesticides and childhood cancer [63].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that prenatal and early life exposures play a role in germ cell tumor carcinogenesis (Chen et al, 2005; Moller, 1997). Type 1 germ cell tumors consist of teratomas and yolk sac tumors that are found in neonates and children <5 years of age and most often are located in the testes, ovaries, retroperitoneum, in the hypophyseal region of the brain, and in the head and neck regions.…”
Section: Discussionmentioning
confidence: 99%
“…For most pediatric GCTs there are no strong epidemiological associations with environmental factors [ 7 ] and no strong genetic associations reported, although both mediasinal and intracranial GCTs are more frequent in patients with Klinefelter syndrome [ 8 ]. In contrast to adult testicular GCTs which frequently demonstrate isochromosome 12p, there are no characteristic cytogenetic abnormalities in childhood cases, although chromosome 1p deletions leading to loss of heterozygosity (LOH) are reported more frequently in childhood malignant GCTs [ 9 ] and array CGH approaches have demonstrated that whilst infant teratomas show no consistent abnormality, in older children changes similar to adult cases, such as chromosome 12p gains, may be identifi ed [ 10 ].…”
Section: Associations Of Paediatric Germ Cell Tumoursmentioning
confidence: 98%